Diketopiperazine and enterotoxin analogues from the mangrove derived-soil Streptomyces sp. SCSIO 41400 and their biological evaluation. Issue 5 (4th March 2022) - Song, Meng-Meng; Xie, Yu-Hui; Chen, Wei-Hao; Hu, Yi-Wei; Zhao, Kai; Liu, Yong-Hong; Huang, Xiao-Long; Liu, Qing-Chao; Wang, Jun-Feng
Abstract: A new diketopiperazine, cyclo-( d -8-acetoxyl-Pro- l -Leu) (1 ), together with eight known compounds (2 –9 ) including three enterotoxins (2 –4 ), four diketopiperazines (5 –8 ) and maltol (9 ), were isolated from the mangrove derived-soil Streptomyces sp. SCSIO 41400. The planar structures of all compounds were determined from analysis of NMR spectra, MS, optical rotation and comparing with literature data. The absolute configuration of compound 1 was assigned by electronic circular dichroism (ECD). The isolated compounds (1 –9 ) were tested for their acetyl cholinesterase (AChE) and pancreatic lipase (PL) enzyme inhibitory activities. Among them, the new diketopiperazine (1 ) displayed preferable PL enzyme inhibitory activity with IC50 value of 27.3 μg/mL, while compounds 2, 5 and 6 showed weak PL enzyme inhibitory activity. Further molecular docking simulation exhibited that compound 1 could be well bind with the catalytic pocket of the PL. Besides, compound 9 showed moderate antibacterial activity against Methicillin-resistant Staphylococcus aureus with MIC value of 12.5 μg/mL, which was comparable to that of the positive control ampicillin with MIC value of 3.125 μg/mL. Abstract : UF0001